Analisis Potensi Nanopartikel Seng Oksida Sebagai Terapi Alternatif Terhadap Uropathogenic Escherichia coli Penyebab Infeksi Saluran Kemih - Kelvin Kohar; Grady Krisandi; Stephanie Amabella Prayogo (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: To date, urinary tract infection (UTI) is still becoming the world’s major health problem that infected 150 million people annually. Uropathogenic Escherichia coli (UPEC) is the most common cause, accounted for more than 80% of total cases. UPEC infection mechanism is supported by many virulence factors owned that contribute in causing antibiotic resistance. Antibiotics are currently used as main pharmacologic therapy for UTI; therefore, treatment failures often occur. The advancement of nanoparticles technology reveals an antimicrobial activity in zinc oxide nanoparticles. Hence, this literature review is written to discuss the potential of zinc oxide nanoparticles as an alternative as well as to help reaching the third 2030 sustainable development goals.Methods: This article was written using the literature review method. We did literature searching by using some keywords in several databases. Inclusions and exclusions criteria were used. The final result yielded 30 studies related to the topic.Discussion: Zinc oxide nanoparticles can be synthesized from Aloe vera plant extraction. In small concentration, 0.3 µg/ml, nanoparticles show an antiadhesion effect by reducing flu and fimH gene expression as UPEC’s virulence factors. The effectivity and safety of nanoparticles in this concentration have also been proven in vitro. Furthermore, in high concentration, these nanoparticles can act as antibiofilm and antibacterial.Conclusion: Zinc oxide nanoparticle has a promising characteristic of antiadhesion, antibacterial and antibiofilm. The safety have also been proven in vitro and in vivo. Both results show a huge zinc oxide nanoparticles potential as an alternative treatment of UTI caused byUPEC. Keywords: Urinary tract infection, Zinc oxide nanoparticle, Uropathogenic Escherichia coli